PENGARUH EFFECTIVE TAX RATE, GOOD CORPORATE GOVERNANCE, DAN BIAYA OPERASIONAL TERHADAP PAJAK PENGHASILAN BADAN: STUDI KASUS PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ashar Basyir; Istichanah Istichanah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Tax is one of the largest sources of income for the state, and one of the subjects is a company or entity. Taxes are one of the factors that are sought by companies to maximize maximum profit. Companies generally will do various ways in order to minimize the company's tax burden. This study aims to identify the effect of the effective tax rate, good corporate governance, and operational costs on corporate income tax simultaneously and partially. The population used is pharmaceutical companies listed on the Indonesia Stock Exchange for the 2017-2020 period. In this study, purposive sampling method was used based on predetermined criteria so that the number of samples was 36 samples. The data analysis method used in this study is multiple linear regression analysis assisted by the Statistical Product and Service Solution (SPSS) Version 26.0 software. The results of this study indicate the calculation of the partial hypothesis test that the effective tax rate and operating costs have a significant effect on corporate income tax. Meanwhile, good corporate governance has no significant effect on corporate income tax. The value of the coefficient of determination (R2) shows that the three variables have an effect on corporate income tax of 85.50% and the remaining 14.50% is influenced by other variables outside of the variables used in this study.